A dynamic simulation study on the sustainability of prefabricated buildings. (February 2022) - Liu, Sha; Li, Zhongfu; Teng, Yue; Dai, Liren
Highlights: TBL theory was used to analyze the comprehensive benefit of prefabricated buildings. System dynamics extracted the correlation between the sub-systems and parameters. Constructing prefabricated buildings improves the utilization rate of resources. Cluster development of the prefabricated building adjust the employment structure. Combined CO2 reduction measures eliminate the boundary effect of single measure. Abstract: With the increase of urban development in China, new construction, extension, renovation, and demolition of prefabricated buildings have also increased, leading to a huge amount of carbon emissions, which poses a great threat to the natural environment and ecological civilization, and goes against the ideas of creating a low-carbon city and sustainable development. How to develop prefabricated buildings efficiently and sustainably is a question governments and environmental organizations around the world wish to solve quickly. However, the sustainable development of prefabricated buildings is an issue with complexity and fuzziness. Thereby, to sustainably develop prefabricated buildings should consider the comprehensive benefits systematically instead of just considering from one certain perspective. In this study, TBL theory was applied to set the boundary of the comprehensive benefits of the prefabricated building system model (CBPBSM), thus the model was divided into three subsystems: economic, environmental, and social. System dynamics (SD) was utilized to identify and quantify the relationships between relevant parameters in the subsystems. This study emulated different scenarios using the CBPBSM and simulated the main parameters with sensitivity analysis. The results indicate that: (1) the greatest advantage of prefabricated building construction is a positive impact on the environment. CO2 emission from the construction of prefabricated buildings is 37% of the emission generated from the construction of traditional buildings. (2) The construction of prefabricated buildings improves the resource utilization rate. When the resource utilization rate increases by 20%, the amount of construction waste will be reduced by 34.55% and the land will be conserved by 29.29%. (3) The development of the market for prefabricated buildings can promote local economic growth. (4) Cluster development of the prefabricated building industry can adjust the employment structure of workers and increase about 132% of their jobs. (5) The quantity of CO2 reduced by applying combined measures is 6.08 times that of applying a single measure. These conclusions can serve as guides for related enterprises and government departments that work with the construction industry and help them create policies to ensure the sustainable development of prefabricated buildings.